Effects of dysfunctional uterine bleeding among women in the selected primary health care facility at Ehlanzeni District, Mpumalanga Province - Mkhatshwa, Ntombizonke Thandeka (My University, 2024)
Dysfunctional uterine bleeding is a worldwide health problem marked by irregular menstrual cycles and excessive bleeding. It affects women all over the world. It affects between 10% and 30% of women in the United States. It is a major public health issue in Sub-Saharan Africa, particularly in South Africa, and is a leading cause of iron deficiency anaemia and gynaecological referrals. According to studies, dysfunctional uterine bleeding has an impact on women's physical, social, and mental well-being, as well as their quality of life. However, there is a lack of awareness among women about the importance of seeking medical and psychological help. This study investigated the effects of Dysfunctional Uterine Bleeding (DUB) through qualitative research. The researcher conducted interviews with 12 women at Nkwalini clinic and analyzed the data using Tesch's Open Coding method. The study employed both exploratory and descriptive designs to gather in-depth information about the experiences of the participants. Measures such as credibility, dependability, confirmability, and transferability were implemented to ensure the trustworthiness of the study. Overall, the research aimed to provide a comprehensive understanding of the effects of DUB and contribute to the existing knowledge in this area. Four main themes emerged from this study: The impact on physical and daily productivity, economic impact, psycho-social well-being, and marital and relationship instability. DUB was found to have a negative influence on women's quality of life in these areas. The study emphasized the importance of prioritizing health to enhance productivity, reduce absenteeism, and promote overall well-being. It also highlighted the need for effective utilization of healthcare services by referring patients to appropriate stakeholders. Ultimately, the study aimed to raise awareness of the challenges faced by women with DUB and advocate for comprehensive support and treatment.
Thesis (M. Nursing)) -- University of Limpopo, 2024
Keywords: Dysfunctional Uterine Bleeding; Qualitative research; Quality of life; Well-being; Menstruation; Uterine circulation; Menstrual cycle